To Adwi and Jadesta: Digitalization of Kalanganyar Village Through Virtual Tour and Tourism Assistance - Herlina Suksmawati; Muammar Alawi; Praja Firdaus Nuryananda (Future Science, 2022)
Kalanganyar Village, located not far from Juanda International Airport, is a fishing tourism destination that is widely known by the people of Sidoarjo. In addition to fishing, in Kalanganyar Village there is a Fish Auction Place (TPI) Kalanganyar which sells the results of fishermen returning from the sea as well as from the results of pond farmers around Kalanganyar. However, tourism development around fishing ponds and seafood restaurants is still not optimally developed. Therefore, the proposing team has the basic assumption that the tourism sector of Kalanganyar Village still has potential assets that have not been developed. One of the potential assets in the village is the potential for riverside tourism which empties into the Bali Sea. Departing from a brief explanation regarding the situation analysis, the community service team can articulate several partner problems, namely a) the absence of strategic planning for the tourism sector in Kalanganyar; b) there has been no development of tourism products and services in Kalanganyar Village; c) there is no unified vision between the village government, village institutions, and the community, and d) there is still a large volume of waste in the tourist area. The proposing team took two priority issues, namely, the stagnation of tourism in Kalanganyar Village, both in terms of goods/services products to tourism planning in Kalanganyar and the unified vision of tourism between village institutions and village communities in Kalanganyar. To answer the problems that have been mentioned, the PIHAT program implemented in Kalanganyar will provide alternative solutions, such as 1) virtual tours and 2) integrated tourism assistance. This community service activity is carried out using the methods of a) virtual tour social counseling as well as virtual tour production, b) asset management training and tourism potential, and c) assistance for tourism activities.